The Effect of Applying the Peer Tutoring Model on Fifth-Grade Students’ Ability to Solve Mathematical Word Problems - Amalia, Rizka; Hayati, Zikra; Herawati, Herawati (International Journal of Research in Mathematics Education, 2025)
Mathematics is one of the sciences that plays an important role in human life. Through learning mathematics, students are trained to think critically, logically, and systematically, as well as to solve the problems they encounter in daily life—many of which are presented in the form of mathematical word problems. Based on initial observations, students' ability to solve mathematical word problems is still relatively low. Therefore, efforts are needed to improve this ability, one of which is through the implementation of the peer tutoring learning model. This research used a quasi-experimental method with a pretest–posttest control group design. The population in this study consisted of fifth-grade students from public elementary schools in the Darussalam sub-district. The sample included 25 students from Ujong Kuta Public Elementary School and 7 students from Tanjung Selamat Public Elementary School. Data were collected using a mathematical word problem-solving ability test. Data analysis was conducted using the Independent Samples t-test via the SPSS application. Based on the analysis of the posttest scores, the Sig. (2-tailed) value was 0.003, which is less than 0.05. These results indicate that the peer tutoring model had a significant effect on the ability of fifth-grade students to solve mathematical word problems.